Pengembangan Alat Peraga “Crander: Crane Dermaga” untuk Menunjang Pembelajaran Fisika Bab Momen Gaya dan Katrol - Illiyyin, Hauriyatul (Jurnal Cerdik: Jurnal Pendidikan dan Pengajaran, 2024)
This study aims to develop the feasibility of learning media based on torque force moments and pulleys using dock crane props. This feasibility is reviewed from the results of the validation of material experts, media experts, and user responses. This feasibility is assessed from the results of validation by material experts, media experts, and user responses. This type of research is Research and Development (RnD) using the 4D model which includes Define, Design, Develop, and Disseminate, but the research is limited to the third stage. Data were collected through a Likert scale-based questionnaire to evaluate the aspects of accuracy, efficiency, aesthetics, and safety of the teaching aid. The research results indicate that the teaching aid "Crander: (Crane Dermaga)" with the learning material on torque moment has an average validation score of 3.23 (good) from material experts and 2.9 (good) from media experts. This proves that the teaching aid "Crander: (Crane Dermaga)" is effective for use in physics learning.